Decree of the President of the Republic of Indonesia No 55/M of 2020 Concerning Termination and Appointment of Membership No After the Supreme Court Decision Number5P/HUM/2021 - Novi Hamzah; Widyawati Boediningsih (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The purpose of this research is to find outpositionNO as an independent institution after the Decision of the Supreme Court Number 5 P/HUM/2021 and the Decision of the Supreme Court Number 5 P/HUM/2021 against the Decree of the President of the Republic of Indonesia No. 55/M, this research method uses normative juridical issues through law by looking at legal norms in force, also aims to reveal the truth in a systematic and consistent manner. Research results The validity of a decision and/or can be seen from 3 aspects, namely authority, procedure and substance which can be tested based on laws and regulations, AUPB, court decisions, and whether or not there is a juridical defect. So that decisions or actions of government administration are declared invalid if they are wrong in terms of authority and declared null and void if they are wrong in terms of procedure and/or substance. Supreme Court decision number 5P/HUM/2021 considers the MENKES Regulation a form of government interference in KKI, so Permenkes Number 81 of 2019 concerning Amendments to Minister of Health Regulation Number 496/MENKES/PER/V/2008 is null and void by law including the Decree of the President of the Republic of Indonesia No 55/M of 2020 regarding the appointment of KKI members for the period 2020 to 2025